Estudo sobre a criação de vínculos afetivos por professores da modalidade EAD - Imperatore, Simone (2020)
The Distance Education (DE) modality has been highlighted in publications related to education due to the new scenarios and roles assumed by teachers and students. The methodological challenges are numerous; theories are built on foundations consisting of collaborative learning, offering autonomy to the student and the teacher. In view of all this change in paradigms that distance education brings in the learning process, one of the most relevant aspects for its success is the relationship between teachers and students in a virtual environment and how it determines the creation of indispensable bonds in this process. The present study aimed to identify the use of methodological actions and procedures that could be performed by distance education teachers to create affective bonds with their students, observing how teachers conduct their courses in order to foster a mediating relationship that values ​​the fundamental human dimensions. It was characterized by a quantitative research, carried out with a sample of 85 university professors who worked in the modality 100% at a distance, through a structured questionnaire. Among the main results obtained, it is highlighted that 54.1% of the investigated teachers worked for more than 9 years in distance education and 70.6% had some specific training to teach in distance learning. It was observed that teacher/student communication was the dimension that most needed attention, that teachers still faced barriers due to technological and personal skills for communication through audio and videos, and that the teacher who already had the experience of being an the student favored greater affection in the development of his classes. The study may conclude that it is up to the teacher to rethink his role in this new context, to undress the conventional methodologies used in his face-to-face classes and to assume the position of mediator in the teaching-learning process, tracing new pedagogical architectures with a view to creating socio-cognitive bonds , affective and emotional, because this is the only way that will enable the meaningful learning of their students.